Dinamika Dakwah di Surakarta Pascagestapu (Gerakan September Tiga Puluh) - Muhammad Isa Anshory; Mulyanto Abdullah Khoir (Pawarta: Journal of Communication and Da'wah, 2023)
Surakarta as a small city, is a very busy market city to offer various beliefs and ideologies. Competition among adherents of these beliefs and ideologies is something that cannot be avoided. After the 1965 PKI rebellion, also known as Gestapu (September Thirty Movement), Muslims faced two challenges to da'wah. First, the latent danger of communism. Second, competition with Christian missions. This paper aims to describe how Islamic leaders respond to these two challenges. The method used the historical method consisted of four stages, namely heuristics, source criticism, interpretation, and historiography. Based on this research, Islamic leaders in Surakarta respond to the challenges of post-gestapu da'wah by collaborating in carrying out various activities, such as activating tabligh, holding Zuhur lectures at the Surakarta Grand Mosque, conveying da'wah messages via radio broadcasts, and carrying out regeneration of da'wah interpreters through madrasah diniyah and Al-Mukmin Islamic Boarding School.